A QUALITATIVE STUDY TO EXPLORE KNOWLEDGE, ATTITUDES AND DIETARY BEHAVIOR IN PREVENTING NUTRITIONAL PROBLEMS DURING PREGNANCY - Ratna Wulandari1, *Ahmad Syafiq2 (Chelonian Research Foundation, 2024)
Anemia during pregnancy is a condition where hemoglobin levels are below 11 gr/dL during pregnancy. In Indonesia, one in two pregnant women experiences anemia. This is exacerbated by the occurrence of chronic energy deficiency during pregnancy. Conditions of anemia and chronic energy deficiency that continue during pregnancy will cause various health problems including the health of the fetus in the womb, even after birth, which has less than optimal growth and development. This research aims to identify determinant factors in preconception nutrition education and develop a framework for preconception nutrition education modules to prevent anemia and chronic energy deficiency during pregnancy. This research method is qualitative by conducting in-depth interviews with pregnant women, women in reproductive health, and health workers which location in Depok City, Indonesia. Data analysis uses thematic analysis. The results show how the importance of education for prospective brides regarding pre-conception nutritional preparation is provided by including elements of ideal pregnancy indicators, balanced nutritious food, and ways to prevent anemia and chronic low energy. The aim of preparing the module was to increase knowledge about healthy pregnancy and avoid nutritional problems, have an attitude that supports nutritional fulfillment and a healthy lifestyle, and have good dietary behavior, especially in regulating food intake. A digital educational media prototype has been created at the following link http://edukasiprakonsepsi.biz.id/Aplikasi_Catin/. The suggestion from this research is that health facilities need to give education about the pre-conception nutritional use of media to make it easier to access information repeatedly. Keywords: Education; Pre Conception; Anemia